ANALISIS PENDIDIKAN KARAKTER ANAK USIA DINI PADA TAYANGAN FILM KARTUN CLOUD BREAD - Zira shafira shafira; Hardiyanti Pratiwi; Samdani Samdani (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2022)
Character education is one form of education that must be introduced to children from an early age because it teaches children to get used to doing good. Character education is not enough if it is only given through teaching. In today's era, social media is one of the media that can help create character education, one of which is YouTube social media. From the youtube application, users can easily access video shows, one of which is cartoons, and parents can use it to provide character education to their children. . One of the cartoons that many children like is the Cloud Bread cartoon, and many parents give this show to their children because of their belief in the character education it contains. Therefore, this study aims to find out what early childhood character education is contained in the Cloud Bread. This type of research is content analysis using the semiotic method of Ferdenand de Saussure, which is a science or analytical method to study signs. This study uses a qualitative content analysis methodological approach. The subject of this research is the cartoon film Cloud Bread, while the object of the research is the education of characters and scenes along with the dialogue of the contents of the film Cloud Bread. The data collection technique used is documentation, and the data analysis technique used is semiotic analysis, namely the science or method of analysis to examine the sign device. The results obtained from this study indicate that the character education contained in the Cloud Bread cartoon is honest, disciplined, hard work, creative, curious, appreciative of achievement, friendly or communicative, peace-loving, fond of reading, social care and responsibility.